Systematic assessment of damage to buildings due to groundwater lowering-induced subsidence: methodology for large scale application in the Netherlands - A. L. Costa; S. Kok; M. Korff; M. Korff (Proceedings of the International Association of Hydrological Sciences, 2020)
In the Netherlands, subsidence of peat and clay soils due to (artificial) lowering of the groundwater table and loading of soft soils is commonplace, causing extensive damage to exposed and vulnerable assets. Awareness of subsidence-related damage to buildings has recently increased in the Netherlands, particularly after reported damages due to the 2018 extremely long dry period. However, despite this being a major concern to homeowners and public authorities, an integrated and systematic risk assessment on regional or national scale is currently lacking which inhibits concrete and meaningful action. In this paper, we propose a methodology for the systematic regional or countrywide assessment of two subsidence-related damage mechanisms to buildings: differential settlement of buildings on shallow foundation, and timber pile degradation due to low groundwater levels. The methodology is set up in a modular, systematic way – initially based on expert judgement and validation with available local detailed information and allows for future improvements. Progress in individual contributing factors to damages can be seamlessly integrated for the systematic improvement of damage estimates. This approach can be replicated for other damage mechanisms and detailed to provide a more local risk assessment. We expect results to be a valuable input for public or private decision making, e.g. in awareness raising and evaluating interventions.